Super simple backyard projects fun & easy animal environment activities - Bernhardt, Carolyn (Minneapolis, Minnesota Super Sandcastle, an imprint of Abdo Publishing, 2017)
Kids will discover plants and animals that live in backyards and read about backyard food chains. Then, they will learn how to create an insect inn, make a squirrel feeder, and more. Each project has color photos and easy-to-follow instructions.
Backyard residents -- Backyard basics -- Habitat food chain -- Materials -- Croak pot -- Bug bed and breakfast -- Bee bath -- Pupsicle -- Squirrel feeder -- Butterfly buffet -- Jar of worms.
105802
Keywords: Habitat (Ecology) -- Juvenile literature; Urban ecology (Biology) -- Juvenile literature; Activity books; Instructional and educational works; Juvenile works; Instructional and educational works; Activity books